Morpho-biochemical characterization and heterosis studies in interspecific derived F1 hybrids of okra (Abelmoschus esculentus) - KIRAN, S BHARGAV; YADAV, RAMESH KUMAR; LATA, SUMAN; SHARMA, BRIJ BIHARI; TOMAR, BHOOPAL SINGH; TOMER, AVINASH (The Indian Journal of Agricultural Sciences, 2024)
The present experiment was conducted during rainy (kharif) seasons of 2021, 2022 and 2023 at vegetable research farm, ICAR-Indian Agricultural Research Institute, New Delhi to study okra [Abelmoschus esculentus (L.) Moench] cv. Pusa Sawani, crossed with 3 wild accessions, viz. A. manihot var. tetraphyllus (IC 90476-1); IC-141055 and IC- 141040 of A. moschatus. A total of 27 morphological and 9 biochemical parameters were characterized for parental species and their derived F1 hybrids. Results showed that the hybrids possessed superior and beneficial traits than the parents and had a greater alliance with their wild parent. The mean performance of the quantitative characters and heterosis of the three interspecific derived F1s differed significantly from parents. Almost all biochemical parameters value, except moisture were found high in wild accessions followed by interspecific derived F1 hybrid and lowest in cultivated variety Pusa Sawani. Per cent disease incidence for yellow vein mosaic virus (YVMV) and enation leaf curl virus (ELCV) was 92 and 32, respectively in Pusa Sawani. However, both the wild accessions of A. moschatus namely (IC-141055) and (IC-141040) and their interspecific hybrids recorded no incidence of both the disease.